Coping strategies and social support needs of experienced and inexperienced nurses performing shiftwork. (28th July 2017) - Gifkins, Jane; Loudoun, Rebecca; Johnston, Amy
Abstract: Aim: The aim of this investigation was to compare perceptions of nurses exposed to short or longer term shift work and their experiences working under this type of scheduling. Background: Shift work is a crucial component of nurses' working lives, ensuring continuous care for patients. This study fills a research gap around the personal experiences of shift working nurses and the strategies used to manage the impacts of shift work. Design: Qualitative case study design. Methods: Constructivist methodology, including in‐depth semi‐structured interviews conducted in 2015, was used for the study. Iterative review and inductive analysis of transcripts from nine recently graduated nurses and twelve experienced nurses enabled identification and verification of key themes. Findings: Three main areas of difference between new and experienced nurses relating to shift work challenges in a nursing environment emerged: perceptions about the utility of working in shifts, coping strategies and social support at home and work. Most experienced nurses found shift work advantageous, especially those with dependents. Coping strategies included flexible shift arrangements in both groups. Experienced nurses detailed the importance of support from family and friends while inexperienced nurses described feeling disconnected from social supports. Experienced nurses cited a lack of support from nursing managers as problematic. Conclusions: Findings suggest shift selection mitigated challenges of shift work for both inexperienced and experienced nurses, indicating autonomous roster selection is critical. Similarly, social support at work from senior nurses and management and at home played an important role in nurses' coping.